Endemic Skunk amdoparvovirus in free‐ranging striped skunks (Mephitis mephitis) in California. Issue 6 (4th July 2019) - Glueckert, Elle; Clifford, Deana L.; Brenn‐White, Maris; Ochoa, Jennine; Gabriel, Mourad; Wengert, Greta; Foley, Janet
Abstract: The genus Amdoparvovirus includes the newly discovered skunk amdoparvovirus and the well‐characterized Aleutian disease virus which causes significant health impacts in farmed mink worldwide. In 2010–2013, an outbreak of fatal amdoparvovirus‐associated disease was documented in free‐ranging striped skunks ( Mephitis mephitis ) from the San Francisco Bay Area of California. To characterize the geographic distribution, earliest occurrence and abundance of this virus, as well as possible impacts on sympatric mustelids of conservation concern, we tested blood samples from skunks throughout California and fishers ( Pekania pennanti ) from northern California for amdoparvovirus DNA. Amdoparvovirus DNA was detected in 64.8% of sampled skunks (140/216), and test‐positive skunks were distributed widely throughout the state, from as far north as Humboldt County and south to San Diego County. The first test‐positive skunks were detected from 2004, prior to the 2010–2013 outbreak. No significant spatial or temporal clustering of infection was detected. Although healthy and clinically ill animals tested positive for amdoparvovirus DNA, histopathologic evaluation of a subset from clinically ill skunks indicated that positive PCR results were associated with pneumonia as well as there being more than one inflammatory type lesion. None of 38 fishers were PCR‐positive. Given the widespread geographic distribution and lack of a clear epizootic centre, our results suggest the presence of an endemic skunk‐associated amdoparvovirus strain or species. However, if the virus is not host‐specific, skunks' ubiquitous presence across rural and urban habitats may pose a risk to susceptible domestic and wild species including mustelids of conservation concern such as fishers and Pacific martens ( Martes caurina ).